The Influence of Adolescent Courtship Behavior on Social Sciences Learning Achievement in Jakarta’s Junior High School - Afifah Faiha Inayah; Desy Safitri; Sujarwo Sujarwo (Journal on Education, 2023)
This research is conducted by the many courtship behaviors of adolescents in the school environment and the dissatisfaction social sciences learning achievement. This study aims to determine whether there is influence of adolescent courtship behavior on social sciences achievement. The research method used is quantitative. Data collection techniques in this study were carried out by observation, questionnaires, and literature studies. The sample of this research was 32 respondents who were taken based on purposive sampling technique. The data processing used is simple linear regression analysis, t test, F test, and the coefficient of determination test. The results showed that the variables of courtship behavior partially and simultaneously had a negative and significant effect on the social sciences learning achievement variable. With the obtained results of the t test, t count -7.222 > t table -2.042 and sig. 0.000 < α 0.05. F count 52.152 > F table 4.15 and sig. 0.000 < α 0.05. R Square value shows a result of 63.5% indicating that the ability of the independent variable to explain the effect on the dependent variable.